Acridine Sensitivity of Bacteriophage T2H in Escherichia coli - Hessler, Anita Y. (1967)
Normally acridine-sensitive, Escherichia coli-T2H complexes are rendered acridine-resistant if the infecting bacteriophage mutant is either pr or q. If these pr or q mutants are treated to produce sensitive revertants, one obtains a mutation at any of several dye-sensitizing (ds) sites in the early enzyme region of the T2 map. The ds mutants are nonspecific suppressors because they reduce the resistance of complexes containing either pr or q to proflavine. The ds mutants are not identical in action, since some make pr or q sensitive to proflavine and quinacrine, and others, to proflavine alone. Two ds mutants have r to r(+) mutation patterns which differ, depending upon whether or not the ds is coupled with r7 (an rII mutant). The mutation patterns of r(+) to r are the same for both ds mutants and for wild type. We suggest that dye sensitization may consist of alterations of early enzymes so as to produce slightly different forms of deoxyribonucleic acid which are in turn dyesensitive.